IODINE, SEAWEED AND FORTIFICATION - Sadan, Smitha (International Journal of Research -GRANTHAALAYAH, 2025)
The advancement of human health is still concerned with science. Many allopathic drugs are produced from substances that are derived from natural products. The capacity of natural products containing compounds considered equal to the medications present in the current scenario has been shown by ancient and conventional medicines in India and abroad. The main sources of natural products are fungi, algae, plants and animals. The current research aims to produce a food that is fortified with seaweed rich in iodine. Seaweeds are recognized to be used in many industries for their useful phycocolloids such as agar- agar, algin, etc. In many countries, including Japan, they are often used as food. Therefore, surveys of seaweed and its chemical composition, ecological cultivation and the method of extraction of essential components are very significant. Most seaweeds are known to absorb iodine, such as brown algae Laminaria, Fucus vesicullosus, Sargassum, etc. If incorporated into foods, these marine algae may contribute to a permanent and natural solution to iodine deficiency disorders. The aims were to research seaweed screening, availability, palatability and other biochemical aspects of available seaweed along the Indian coast. Fortification of seaweed food can lead to a product that is high in iodine other than fortified salt and without any side effects as well.